Orofacial pain resembling hypnic headache: A case report - Noboru Imai; Asami Moriya; Eiji Kitamura (SAGE Publishing, 2020)
The International Classification of Orofacial Pain (ICOP) classifies orofacial pain resembling primary headache as orofacial migraine and tension-type, trigeminal autonomic, and neurovascular orofacial pain. We used the ICOP classification style to make a diagnosis on a 76-year-old woman with orofacial pain, which developed only during sleep three times per week, caused awakening, and lasted 3-4 h without cranial autonomic symptoms or restlessness. Except for the pain area, her symptoms fulfilled the diagnostic criteria for hypnic headache. We diagnosed her with orofacial pain resembling hypnic headache. We should review the cases of such patients and classify them according to the ICOP.